PENGEMBANGAN GOOGLE SITE SEBAGAI MEDIA PEMBELAJARAN PADA MATERI BERNYANYI UNISONO DI KELAS VII SMP ISLAM PARISKIAN KOTA SERANG - Elsa Muthia Elsa; Suhaya Suhaya; Fuja Siti Fujiawati (Pendidikan Seni Drama Tari dan Musik, Universitas Sultan Ageng Tirtayasa, 2022)
Abstract: Learning art and culture is learning that is closely related to practical learning. Students will find it difficult to understand the material if they only learn through writing in the book, while in arts and culture subjects such as singing Unisono material, it must be visualized. Website-based learning media is an alternative to support the process of learning activities so that they can be accessed anytime and anywhere. This study aims to determine the process of developing the google site as a learning medium, to determine the feasibility of the google site as a learning medium and to determine the response of students to the google site as a learning medium for the unisono singing material in class VII. The research method used is research and development (R&D) with the ADDIE development model (analysis, design, development, implementation, evaluation). From the validation process carried out by media experts with a percentage of 83.7% belonging to the